Pengakuan Dan Perlindungan Hukum Hak Masyarakat Adat Atas Tanah Ulayat Dalam Upaya Pembaharuan Hukum Nasional - Hayatul Ismi (Jurnal Ilmu Hukum, 2012)
Land is represent one of very elementary asset stateof Indonesia because state and nation live and expandabove land. Society of Indonesia position land atdimiciling very important, specially in society cus-tomary law. But, up to now not yet been made avai-lable by a complete information about unfolding andboundary of region included by various customarylaw of mentioned in this matter is customary right forland rights. This handing out conclude that rights ofcustomary right for land in law of Indonesia confessedby through fundamental code of agraria that is UUNo. 5 year 1960. In this case the confession given bya state have the character of laminated and condtionalbecause confession given to society of customary lawand rights of its customary right for land.